THE DETERMINANTS OF LEADERSHIP, WORK MOTIVATION, AND ORGANIZATIONAL CULTURE ON EMPLOYEE PERFORMANCE - Muhammad Zhahir Akmar; Buyung Sarita; Agustinus Tangalayuk; Usman Usman (Jurnal Multidisipliner Kapalamada, 2025)
This study aims to analyze the influence of leadership, work motivation, and organizational culture on employee performance, both simultaneously and partially. The research was conducted at the Protocol and Regional Leadership Communication Division of Konawe Kepulauan Regency, involving all 65 employees as respondents using a census sampling technique. Data were collected through questionnaires developed based on the indicators of each research variable. The data were analyzed using multiple linear regression with the assistance of statistical software. The results indicate that leadership, work motivation, and organizational culture simultaneously have a positive and significant effect on employee performance. Partially, leadership, work motivation, and organizational culture also demonstrate positive and significant effects on employee performance. These findings emphasize the importance of effective leadership, strong work motivation, and a supportive organizational culture in enhancing optimal employee performance.